Problematika neustrezne kakovosti pitne vode na kraškem območju in možne rešitve - Drev, Darko (Gradbeni vestnik, 2013)
One prominent feature of the Karst areas is the lack of sharp boundaries between surface water and groundwater. As a consequence, surface water contamination quickly results in a decrease in the quality of groundwater. If adequate compliance with sanitary engineering principles is not ensured, underground drinking water reservoirs may be easily contaminated. This is particularly evident during periods of significant precipitation, when water becomes cloudy. Our analysis of the composition and size distribution of particles in cloudy water showed that membrane filtration is the preferred method for the resolution of this problem.
Keywords: karst; Kras; kvaliteta; pitna voda